Sources of innovation in dairy production in Kenya - Schreiber, C. (International Service for National Agricultural Research, 2002)
In times of market liberalization and structural adjustment, the agricultural sectors of developing countries face profound changes. To seize new market opportunities, farmers need to innovate-to become more efficient producers and effective entrepreneurs. In order to innovate, farmers need new technologies and information on how to access and manage them, as well as better support services for the delivery of inputs and knowledge, and better infrastructure for delivering produce to the market. Structural adjustment policies, however, have led to sharp reductions in public-sector research and extension services, on which farmers have come to rely as their principal sources of innovation. Can the private sector step in to provide these services? Is there a continuing role for public-sector actors? And, if so, how will private- and public-sector players interact? This Briefing Paper presents a case study of a dairy production venture in Kenya that sheds light on these questions. Kenya's dairy subsector is already changing: a buoyant market for dairy products offers producers an opportunity to increase their income and an incentive to invest in new technologies; in response, market-oriented institutions are evolving and private-sector service providers are stepping into the arena. But market development is more advanced in some areas than in others, providing an opportunity to gain insights into the process of change by comparing more- and less-developed areas.